Sustained metabolic reduction and hypothermia in humans - Katharyn L. Flickinger; Alexandra J. Weissman; Francis X. Guyette; Ryann DeMaio; Andrea Jonsson; Victor Wu; Jenna L. Monteleone; Emma A. Zurowski; Jonathan Birabaharan; Daniel J. Buysse; Philip E. Empey; Thomas D. Nolin; et al. (PLoS ONE, 2025)
Metabolic reduction is an adaptation employed by animals encountering environmental stressors or scarce resources. Lowering metabolism in humans may be useful to reduce consumables, oxygen utilization and carbon dioxide excretion. This is relevant for payload optimization or resource-restricted scenarios such as long-duration spaceflight or austere terrestrial environments (e.g., Arctic/Antarctic, submarine, cave or mine extraction). We previously demonstrated intravenous and single oral or sublingual doses of dexmedetomidine reduce oxygen consumption, wakefulness, and core body temperature in healthy humans. However, longer-acting dosing strategies are required to achieve greater levels of metabolic reduction. We explored whether a sublingual loading dose followed by subcutaneous infusion (SQI) of dexmedetomidine with and without surface cooling can decrease metabolic rate for 6 hours. We recruited 11 healthy volunteers, 4 male, median age 23 (IQR 21–25), who completed one-day laboratory studies measuring core body temperature via telemetry and metabolic rate via indirect calorimetry. Participants consumed an oral loading bolus of dexmedetomidine (2 μg/kg) followed by a six-hour SQI of dexmedetomidine (1 μg/kg/hr). Surface cooling pads were placed on the backs of 7 participants to promote heat loss. We collected vital signs continuously and monitored participants until they could be safely discharged. Energy expenditure (EE; kcals per day) dropped from baseline regardless of surface cooling. With surface cooling, median temperature decreased from 36.9°C (IQR 36.7–37.0°C) at baseline to 35.4°C (IQR 35.3–35.5°C) at 6 hours. Sublingual loading dose followed by 6-hour SQI of dexmedetomidine safely and effectively reduces metabolic rate. Future studies should be evaluating the effectiveness of SQI dexmedetomidine without a sublingual loading bolus, evaluating novel administration methods, and determining if tolerance develops with long-term use.